"Eat", "eclipse" and "adorn": cognates in Chinese - Goertzen, Stanley (2024)
This essay addresses the need for a radical departure in the making of Chinese-English dictionaries. What is notably missing from current dictionaries, as well as from serious western works in Chinese linguistics, such as Karlgren's Grammata Serica, is the ability to cross reference the key words and synonyms used in the Chinese lexicographic sources. This essay particularly attempts to demonstrate the importance of tracing the semantics of a word family by examining the trail of synonyms and reformulating the underlying semantics accordingly. Additionally, this essay stresses the importance of understanding and using traditional Chinese lexicographic sources. Computer databases offer a convenient means for entering Chinese synonyms and definitions in a romanized ASCII format, along with easy and quick access to them. The Old and Middle Chinese forms used here are a proposed "logical" and ASCII substitution for Karlren's ad hoc and diacritical-laden "reconstruction".